2020
DOI: 10.1108/jocm-02-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to change and turnover intention: a moderated mediation model of burnout and perceived organizational support

Abstract: PurposeThe purpose of the paper is to study the turnover intention of employees during the phenomenon of resistance to change. The paper examines the mediating role of burnout in the relationship of resistance of change to turnover intention and the moderating role of perceived organizational support in this relationship.Design/methodology/approachThe empirical data of the study has been collected via cross-sectional data collection method and include responses from 410 employees. The moderation mediation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 78 publications
3
44
0
1
Order By: Relevance
“…For instance, our data suggested that mattering did not have any direct effect on turnover intention. This is inconsistent with some findings, such as the one by Richards et al [4], Haizlip et al [28], as well as Reece et al [3], who stated that the sense of mattering at work predicts the general mental well-being at work, protect the employees from burnout and work-related stress, two main predictors of turnover intention [5], [35]- [37]. In our defense, despite we agree that mattering holds a key role in mental health at work, we did not try to prove it any further.…”
Section: Discussion and Implicationmentioning
confidence: 74%
“…For instance, our data suggested that mattering did not have any direct effect on turnover intention. This is inconsistent with some findings, such as the one by Richards et al [4], Haizlip et al [28], as well as Reece et al [3], who stated that the sense of mattering at work predicts the general mental well-being at work, protect the employees from burnout and work-related stress, two main predictors of turnover intention [5], [35]- [37]. In our defense, despite we agree that mattering holds a key role in mental health at work, we did not try to prove it any further.…”
Section: Discussion and Implicationmentioning
confidence: 74%
“…The review is based on “Resistance to change and turnover intention: a moderated mediation model of burnout and perceived organizational support” by Srivastava and Agrawal (2020), published in Journal of Organizational Change Management. The purpose of this study is to examine the turnover intention – resistance to change relationship, the mediating role of burnout on this relationship and the moderating role of perceived organizational support.…”
Section: Commentarymentioning
confidence: 99%
“…A research paper by Srivastava and Agrawal (2020) examines the turnover intention – resistance to change relationship, the mediating role of burnout on this relationship and the moderating role of perceived organizational support. Data was gathered from the responses of 410 managers employed in private organizations from the Delhi NCR region of India to a questionnaire survey.…”
mentioning
confidence: 99%
“…A critical factor in organisational change is the attitude towards change or resistance to change (Pardo del Val and Martinez, 2003; Erwin and Garman, 2010; Smollan, 2011). Attitude towards change (ATC) has become a very important issue in public organisations lately (Ford and D'Amelio, 2008; Pieterse et al ., 2012; Srivastava and Agrawal, 2020) and includes the affective, behavioural and cognitive components (Oreg, 2006). We argue that attitude towards change acts as a boundary condition for the link between OCC and organisational performance.…”
Section: Introductionmentioning
confidence: 99%